Pasar Sepuran di Mata Masyarakat Desa Pagerdawung - Kartika Satya Noviafitri; Atiqa Sabardilla (Peneliti.net, 2023)
Surprise market is a culinary tour that is in great demand on weekends. One of the culinary destinations that are liked by all circles. This study aims to determine the potential of the sepuran market in Pagerdawung Village, how the market has caught the attention of the local community so that it prefers the sepuran market as a traditional market compared to modern markets such as supermarkets and online markets. The method used is descriptive qualitative method and data collection used is in-depth interviews and observations. The results of the study: (1) Sepuran Market is the result of the development of traditional markets. The community's thinking continues to develop, giving rise to the Sepuran Market as the fruit of the Pagerdawung community's creative thinking. Sepuran Market consists of various kinds of culinary delights. (2) Sepuran Market has positive and negative impacts that complement its presence in Pagerdawung Village. (3) In the era of modernization, Pasar Sepuran is unable to compete with modern markets. Apart from losing in cleanliness, they also lost in terms of permits for places to practice buying and selling.